1984
DOI: 10.1152/ajpheart.1984.246.1.h80
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II attenuates baroreflex control of heart rate and sympathetic activity

Abstract: We determined whether angiotensin II (ANG II) modulates the arterial baroreflex control of lumbar sympathetic nerve activity (LSNA) in chloralose-anesthetized rabbits. Intravenous infusion (iv) of ANG II caused significantly less reflex bradycardia and less inhibition of LSNA than iv phenylephrine (PE) for equivalent increments in arterial pressure. During a background iv infusion of ANG II, which caused a small sustained increase in arterial pressure, the reflex inhibition of heart rate (HR) and LSNA in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
106
5

Year Published

1987
1987
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 0 publications
12
106
5
Order By: Relevance
“…It is known the attenuating effect of angiotensin II on baroreflex sensitivity. 24 Moreira et al 25 have reported the existence of a close relationship between overactivity of renin-angiotensin system and the impairment of baroreflex control of heart rate in rats with renal hypertension. Reduction in baroreflex sensitivity present in the acute phase of 2K 1C hypertension in rats is mediated, at least in part, by renin-angiotensin system activation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known the attenuating effect of angiotensin II on baroreflex sensitivity. 24 Moreira et al 25 have reported the existence of a close relationship between overactivity of renin-angiotensin system and the impairment of baroreflex control of heart rate in rats with renal hypertension. Reduction in baroreflex sensitivity present in the acute phase of 2K 1C hypertension in rats is mediated, at least in part, by renin-angiotensin system activation.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have observed that ANG II decreases baroreflex sensitivity while blockade of the renin-angiotensin system increases it (7,9,12,19,34). Others have observed resetting with no change in sensitivity (9,13,24,30).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that ACE inhibitors, more than antirenin immunization, reduce the generation of angiotensin II within the central nervous system, where it specifically depresses cardiac baroreceptor reflex responses to increases, but not to decreases, in blood pressure. 27 - 28 However, it has been recently shown that brain ACE was not consistently decreased by most of the ACE inhibitors. 29 In addition, antirenin immunization also tended to increase the baroreceptor reflex sensitivity.…”
Section: Figure 4 Bar Graphs Showing the Free Urinary Catecholaminesmentioning
confidence: 99%